Development of Low-Fat Functional Pork Nuggets with Incorporation of Whey Protein Concentrate : 10.5958/2581-6616.2020.00006.7 - Jangir, Apeksha; Malav, Om Prakash; Chatli, Manish K.; Mehta, Nitin; Wagh , Rajesh V. (Journal of Meat Science, 2021)
Three different levels of whey protein concentrate viz. 3%, 5% and 7% were incorporated as fat replacers in pork nuggets after replacing the fat in the prestandardized formulation of pork nuggets and were compared with high fat control with 10% added fat. The control and treatment products were analysed for physicochemical parameters, proximate composition, instrumental colour profile, texture pro file analysis and sensory evaluation. The pH of the treated pork nuggets incorporated with whey protein concentrate was significantly (P<0.05) lower than the control. Cooking yield, moisture, protein and ash followed an increasing trend on incorporation of whey protein concentrate. The fat content was significantly (P<0.05) reduced among all the treatment products. The values for the most of instru mental colour profile and texture profile were comparable among the control and treatment products. Sensory scores for all parameters were awarded significantly (P<0.05) higher for the pork nuggets incorporated with 5% whey protein concentrate in comparison to other treatment products.